Hubungan Antara Partisipasi Masyarakat, Pembentukan Undang-Undang dan Judicial Review - Riza Multazam Luthfy (Prodi Siyasah (Hukum Tata Negara) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2019)
Community participation in national and state life today is an important study. This is because in a democratic country, public policy cannot be separated from public participation. This study seeks to discuss the relationship between community participation, the making of Act and the implementation of judicial review. The results showed that: (1) Public participation in the making of Act and the implementation of judicial review can: (a) Provide a better basis for public policy making in creating good governance. (b) Increase citizens' trust in the executive and legislative branches. (c) Save human resources, because with the involvement of the community in public policy making, the resources used in public policy socialization can be minimized. (2). Community participation in evaluating Act becomes an important activity, in order to establish control whether an Act is in accordance with its objectives or not. The public can submit a judicial review to the Supreme Court (MA) or the Constitutional Court (MK) if they judge that their rights have been impaired by certain Act. (3). The relationship between community participation and the making of Act and the implementation of judicial review is very close. Without community participation, the Act produced does not reflect the interests of the community and only prioritizes the interests of certain groups. The Constitutional Court (MK) and the Supreme Court (MA) will not conduct a judicial review if there is no request from the public.